2008
DOI: 10.1007/s10533-008-9184-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of foliar Ca/Sr discrimination and 87Sr/86Sr ratios to determine soil Ca sources to sugar maple foliage in a northern hardwood forest

Abstract: Calcium/strontium and 87 Sr/ 86 Sr ratios in foliage can be used to determine the relative impor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…8a and 10a). The differences between Sr/Na and Ca/Na ratios could reflect lithologic heterogeneity and/or preferential biological Ca cycling (Blum et al, 2008).…”
Section: Lithologic Controls On Concentration-runoff and Ratiorunoffmentioning
confidence: 99%
“…8a and 10a). The differences between Sr/Na and Ca/Na ratios could reflect lithologic heterogeneity and/or preferential biological Ca cycling (Blum et al, 2008).…”
Section: Lithologic Controls On Concentration-runoff and Ratiorunoffmentioning
confidence: 99%
“…Moreover, a recent survey shows that despite some recovery of surface waters, current inputs of acidic deposition are still resulting in the net loss of exchangeable Ca, with equivalent increases in exchangeable Al in Ca-poor watersheds across the Northeast USA (Warby et al, 2009). Many soils in this region are developed on Ca-poor silicate rocks that undergo weathering at a rate too slow to readily replenish Ca lost from the exchange pool (Likens et al, 1996;Nezat et al, 2004;Blum et al, 2008). It has been suggested that Ca may become a limiting nutrient for vegetation and at low levels may contribute to a decline in the health of some plants and animals in the region.…”
Section: Acid Deposition and Camentioning
confidence: 99%
“…Therefore, one of the primary research interests in forest nutrition science is the identification of bioavailable Ca sources in the soil-plant-atmosphere system. Thus far, a common way to identify the sources of Ca in forest ecosystems was with the application of indirect tracers, such as strontium isotopes ( 87 Sr/ 86 Sr) or elemental Ca/Sr and Ba/Sr ratios (Miller et al, 1993;Bailey et al, 1996;Capo et al, 1998;Kennedy et al, 1998Kennedy et al, , 2002Blum et al, 2002Blum et al, , 2008Poszwa et al, 2004;Bullen and Bailey, 2005;Drouet et al, 2005a,b;Dasch et al, 2006;Drouet and Herbauts, 2008;Nezat et al 2010). …”
Section: Introductionmentioning
confidence: 99%